Obtenção de imunoglobulina G em leite, creme, manteiga e leitelho pelo método gravimétrico - Juliana Soares Lima (2017)
Milk proteins are known for their high nutritive value and functionality. The objective of the current study was the development of a method to obtain milk and derivatives fractions with high immunoglobulin concentration, based on gravity (milk, cream, butter and buttermilk). Immunoglobulin detection was done by SDS-PAGE. The richest fraction of Immunoglobulin was found in cream after gravity separation from raw milk at 4oC during 24 h, compared to the cream obtained by centrifuge separation. In the cream of the raw milk obtained by the centrifuge separation was found 1,56% of IgG, in the cream of the raw milk kept 24 hours without agitation, was 4,46%. The cream obtained using centrifuge separation from pasteurized milk contained 0,60% of IgG, while cream obtained from pasteurized after 24 hours without agitation was 8,14%. After cream phase inversion, immunoglobulin partition occurred in the butter and whey butter. Therefore, it is possible to obtain cream fraction with high immunoglobulin concentration, but further studies are necessary for process scale up.